(untitled) (Journal of the College of Education for Women, 2019)
The curriculum balancer (comparative) (comparative linguistics), of greatimportance in studies of language in general, and study any phenomenon ofacoustic phenomena, morphological, syntactic and semantic study of balance in theArabic language in the light of the dialects of the Arabian Peninsula, leading tosignificant results in linguistic research, which could achieve Some issues that werenot up to where the old research conclusive results, and helps to explain things mayhave created confusion if it did not mean the budget in the interpretation of thestudy, as well as its importance in the origination of phenomena of language andreasoning on the same phenomenon, followed by the Sisters Arab Veseltha.Hence, it is my desire to study voice (daad) between Arabic and dialects of theArabian Peninsula study the budget, has launched the word (accents), and no less(languages), because the Arab and sisters are only accents Ancabt of a nativespeaker, but dispersed in different , led to the existence of different dialects fromeach other in the faces, and resemble each other in other respects, much closer thebonds of their relationship, and the farther diverge.The study was divided in my research into two sections: Section I: daad voice inArabic (Classical) at the ancient and modern, and the second topic: the study byArab Voice Arabic (classical) and dialects of the Arabian Peninsula study budget.Research has resulted in many important results, research revealed it in place,including:1. The (daad) eloquence (Alacetkakih side), which he described Sibawayh welldescribed (daad vulnerable), the voice of a composite of signifier Emphatic and theharvest side, has proved Find indication of historical studies to the voice (by Arab), which was originally a voice soft Ahtkakia, which confirms accuracy of thedescription Sibawayh to this voice, that voice soft (fricative), Mjhor, and directorof the first edge of the tongue and following of the molars, a voice honored withthe elongation of the director, that is, friction sound side, and pronunciation(lateral) to the voice of daad / d /, it offset in the dialects of the Arabian Peninsula,in the dialect of Akkadian rulda’u) Rldae) and Rulta’u) Rltae), the name of the Arabidol (satisfaction (Ruda>.2. It has been observed from the description (Sibawayh), that (daad weak) does notcome out of the adoption of the back of the tongue from the side of the molars, inthe region of maximum palate (Kaldhad eloquence), but based on the edge of thetongue at the point of more advanced, towards the roof of the palate on the frontteeth, whether the focal from the right or the left, leaving the air comes out of thearea that does not anchor them, and prepare the back of the palate of the occlusion,ie, that there is a shift from (daad eloquence) to (daad weak), and (daad vulnerable)pronunciation (between daad and Za) He also explained (the son of living), andvoice convergence WYSIWYG substitution process between them, and mixing ofthe two images that led to the transition exit (daad) to (Za), and switched voice (byArab) to (Za) and to the other sounds was due to difficult.3. Retained the voice (by Arab) as well as Arabic (classical) of the sisters sisters ofVeseltha: tone Sabaean and Arabic dialects Southern dialect and the Safavid (anArabic dialects North extinct), it is the form and spoken, was contained in theassets of her words, corresponding to the words contained in the Arab (classical)sense of himself.4. Occurred in the sound (by Arab) / d / sound shifts, turned to the voices,including: -A - shift (by Arab) to (Zae): The result of the evolution of sound (by Arabeloquence) of old, and turned to exit the front, while maintaining such friction,which led to pronounce the word one two passport Ntqatin, Baldhad and Za,indication of taking the same, and they are many in Arabic dictionary, I found thisconfusing reality in Arabic between (daad) and (Za) roots in tone Ugaritic: it isfound in a slab of panels Ugaritic that he wrote it all (Z) and responded (Za), to: (jŮ h s : laughs), and (r A, is an act of washes, that is out) and (j m AA: a go), hasbeen demonstrated in the place of research ().B - shift (by Arab) to (I): it was from the results of development of the audio hit(by Arab eloquence) of old, that have evolved to (daad weak), and in spite of thisdevelopment, except that (daad) are still difficult pronunciation; therefore turnedmultiple voices to the voice (Tae), including, as evidenced by the words of Ibn live:((by Arab and vulnerable people Aatast language on them, then maybe I droppedher, and that they give it the tip of the tongue, and the parties folds)) (). Has beenreported elsewhere in an example of the replacement (by Arab) (I): "Money toErtah Hakv Valtdja...... and tells Atdja, Vibdl of daad I." (). There have been examples of this type of substitution in Arabic (Classical): Medallions andAlonoad, and examples of many other others, received in place of research (), hasbeen found for this type of replacement assets in the tone of Sabaean dialects of theSouth Arabian, and they share with the classical Arabic in This type ofreplacement, but it is restricted replacement Sabaean dialect, that: (b s z), ie agentsarmed, and (s b i) replacement by Arab I, and (Z m and n), that is: home, home.And Btae, which is the parent (m i and n) the same sense, has been proven in placeof research ().C - converted (by Arab) to (R): it has evolved (daad weak) does not (by Arabeloquence), because it is more advanced toward the roof of the palate of (daadeloquence), which is based in the edge of the tongue on the front teeth, so it cansay: it is turned to the voice of (antibiotic), as it turned Arab in many stylesAlastamalah to convert voice (daad) difficult pronunciation, the voice (antibiotic) iseasier spoken, and this is Theloana audio Olovonya, and exemplified in Arabic aremany, has gone through voice (by Arab) operations multiple audio, and witnessedthe disturbance led to change his image, it has replaced (Sada) in most dialects ofthe Arabian Peninsula, word (Sheep) in Arabic (classical), offset in Akkadian:(senu) Balsad, and (land in Arab, offset in Akkadian , and Ugaritic, Phoenician andAlmaabih (> rs) Balsad, has been demonstrated in the place of research ().D - transformation (daad) to (G): it became (by Arab vulnerable) transformed from(daad eloquence), because of the difficulty, to the voices, the voice (Zai) of them,and I see it is not (Zaya) pure, but is (Z tinged voice Zai), launched by the label(daad Zaúah), ie, that there is a disturbance happened in the pronunciation (daad) atsome point in the life of the Arabic language, has led to its transformation to thevoices of many, was the voice of (Zai) is not pure, and one of them, from inSabaean and Ethiopian dialects: (n z p) in the sense: Ajtrah, right, harm, and (n g p)the replacement of the same sense (daad) (Zaya) ().E - conversion (daad) to (L) for the participation of (lam) with (daad) in a part ofthe director, and he (the edge of the tongue), has pointed to this Sibawayh in hisdescription (by Arab eloquence) (old side), I see that (daad eloquence) side of thecompound converts voice Emphatic and the harvest side, and that (the harvest) ispart of the speech composite Z eloquence of old, with evidence that some Arabsused to say: (Tdja) instead of (lie down).I have found for this type of replacement extension in Arabic dialects south ofmodern, as altered (by Arab) (Lama Mfajma) in my accent (Dthena) and (Shibuya),as they say: (Orel arL) replacement (daad) (Lama), and (Lua (Law <, in (theme),meaning: the owners of the same tribe, has been demonstrated in the place ofresearch ().